(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This study examines the semantic range and conceptual development of the Indo-Iranian term mitra as reflected in Avestan and Vedic sources. It focuses on the dual nature of the term, which encompasses both the narrow juridical meaning of “contract” or “promise” and the broader sense of “alliance” as a binding social and moral relationship. Through textual analysis of Avestan passages, particularly those presenting hierarchical and functional classifications of miθra, the research highlights the term’s role in structuring interpersonal, familial, and political relations. The study further explores the linguistic expressions associated with the establishment and violation of miθra, demonstrating its significance as a formalized and enforceable bond. Comparative evidence from Vedic traditions supports the interpretation of mitra as a concept grounded in reciprocity and obligation. The evolution of the term in later linguistic stages, where it acquires meanings such as “friend” and “love,” is also considered in light of its original semantic core. The analysis situates mitra within the broader Indo-Iranian worldview, emphasizing its function as a foundational principle of social cohesion and moral order